2021
DOI: 10.1097/ncc.0000000000000920
|View full text |Cite
|
Sign up to set email alerts
|

Correlation Between Symptom Clusters and Quality of Life in Children With Acute Leukemia During Chemotherapy

Abstract: Background: Children with acute leukemia experience various distressing symptoms due to the disease and its treatment during chemotherapy. These symptoms cluster together and have negative impacts on patient outcomes. Objective: The aim of this study was to examine symptom clusters that children with acute leukemia undergoing chemotherapy are experiencing and the impact of these symptom clusters on their quality of life.Methods: A cross-sectional study design was used, and 184 Chinese children with acute leuke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 45 publications
0
11
0
Order By: Relevance
“…Furthermore, regarding the neuropathy SC, we concluded that a lack of energy (fatigue) was the most common symptom and the second most severe and distressing symptom; this symptom can be encountered at any stage of AML and is not alleviated by adequate sleep or rest. Loss of energy may also predict other symptom conditions, as it is linked to a variety of physiological symptoms/factors, such as anemia, malnutrition, pain, sleep disturbance, and decreased immune function, as well as psychological symptoms, such as worrying, depression, nervousness, and sadness [39][40][41] .…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, regarding the neuropathy SC, we concluded that a lack of energy (fatigue) was the most common symptom and the second most severe and distressing symptom; this symptom can be encountered at any stage of AML and is not alleviated by adequate sleep or rest. Loss of energy may also predict other symptom conditions, as it is linked to a variety of physiological symptoms/factors, such as anemia, malnutrition, pain, sleep disturbance, and decreased immune function, as well as psychological symptoms, such as worrying, depression, nervousness, and sadness [39][40][41] .…”
Section: Discussionmentioning
confidence: 99%
“…However, pain, anxiety, and fatigue scores in this study were lower than in a previous one. 13 On the one hand, it may be due to the different severity of symptoms reflected by different assessment tools, especially the different ages of children and the different understanding of the health concept measured, which may affect the consistency of measurement results to some extent. On the other hand, several studies have shown differences in the outcome of symptoms reported by children and parents, which may be related to parents' overestimation of pain, anxiety, fatigue, and other symptoms experienced by children.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have found that children with AL have somatic, gastrointestinal, emotional, and self-image clusters. 13 , 14 , 15 More than 40% of children with AL will develop the pain, anxiety, fatigue, and sleep disorder symptom cluster (PAFS cluster) during chemotherapy, which accounts for about 75% of the children's lives. 16 , 17 A study by Cheng et al 18 demonstrated that the PAFS cluster was moderately correlated with functional status and quality of life.…”
Section: Introductionmentioning
confidence: 99%
“…Symptom research has focused on examining characteristics such as prevalence, intensity, timing, and clustering, yet less research has explored the dimension of distress and how this impacts the child's symptom experience (Li et al, 2023; Wang et al, 2023; Yeh et al, 2009; Zhukovsky et al, 2015). Symptom distress as defined by McCorkle and Young (1978) is the patient's report of their degree of discomfort related to the symptoms they experience This study seeks to gain insight into the interrelationships between reported symptom distress and mood in children with severe illness by conducting a network analysis (NA) on a sample of children receiving treatment for cancer.…”
Section: Introductionmentioning
confidence: 99%